Action Research and Tutoring in the Learning Community: New Implications for Online Adult Education - Crosta, Lucilla; McConnell, David (Proceedings of the International Conference on Networked Learning, 2006)
This paper presents some reflections on a study carried out as research student at the Department of Education, Sheffield University (UK). The research context is a post-graduate blended Master in Open Education and Training (MOET) carried out at the Bocconi University in Milano (Italy) in year 2004. The blended course was delivered partially via distance (online) and partially in presence (face-to-face). The study overall is presented as an Action Research approach where the teacher/tutor’s personal online experience leads to considerations about possible ways to improve the learning process in online learning communities at post-graduate level.